Extraosseous multiple myeloma: Imaging features - Moulopoulos, L.A.; Granfield, C.A.J.; Dimopoulos, M.A.; Kim, E.E.; Alexanian, R.; Libshitz, H.I. (American Journal of Roentgenology, 1993)
Multiple myeloma is a disseminated malignant neoplasm usually derived from a single clone of plasma cells. Patients with myeloma have diverse signs such as anemia, hypercalcemia, uremia, pathologic fractures, and recurrent infections. Extraosseous manifestations are found in less than 5% of patients with multiple myeloma. They can arise in any tissue, and their presence has been associated with more aggressive disease. The purpose of this assay is to illustrate the imaging findings of extraosseous myeloma and heighten awareness of this unusual manifestation of multiple myeloma.